Proposed interior design scheme of Sani Express Office for Sani Express Sdn. Bhd. at Lot 4122-4123 Jalan Sultan Idris Shah, 32000, Lumut, Perak / Muhammad Rafiuddin Ab Rashid - Ab Rashid, Muhammad Rafiuddin (Faculty of Architecture, Planning and Surveying, 2011)
Project report is one of important subject that be taken by each student part six (06) in Diploma Interior Design or student last year in order to graduate. The objective of doing project report is to give student a foundation of understanding by broadening their knowledge of spatial design through the study of the plan and plan language.This cources will make student practice to some research based on their project proposal. Student also should fulfill all the requirement needed and must follow the stage. This project report is about new proposal which is Proposed Interior Design Scheme Of Sani Express Office For Sani Express Sdn. Bhd. at Lot 4122-4123 Jalan Sultan Idris Shah, 32000 , Lumut, Perak. In this report, the whole new look and image of Sani Express Sdn. Bhd. is proposed smoothly according to the design process and material presented through reading, lecture and design projects. This proposal which reflects the whole new look of Sani Express new office covers every department beginning from the reception, workstation to staff lounge. It is proposed for Sani Express to have the “Transparent through Modernity” concept which is fully based on their company’s profile, design portfolio and company’s logo which is in white, red and black letterings that defines a design-oriented approach to their business yet gives greater visibility in the market.